Closed-loop Battery Aging Management for Electric Vehicles. Issue 2 (2020) - Pozzato, Gabriele; Corno, Matteo
Abstract: In this work, a closed-loop battery aging management strategy for electric vehicles is proposed. The aging management strategy, following the model predictive control rationale, optimizes aging and vehicle performance online. The proposed formulation is based on a closed-loop term which aims at tracking a user defined aging profile. A thorough simulation study validates the approach and verifies its robustness against model uncertainties and anomalous aging phenomena.